Relationship between bottle feeding in supine position in infants and the presence of asthma among preschoolers - Pertiwi Febriana Chandrawati; Roni Naning; Ekawaty Lutfia Haksari (Paediatrica Indonesiana, 2009)
Background Asthma is a common chronic respiratory disease.The risk factors of asthma are allergic factors, familial atopy,race, gender, and smoking during pregnancy. Other risk factorsare gastroesophageal reflux and micro-aspiration which causebronchospasm and bronchial hyperreactivity due to repeatedairway irritation.Objective To determine the association between bottle feedinggiven in supine position before sleep time in the first year of lifewith asthma in 4 to 7 years old.Methods A case control study was conducted on pediatricpatients from Sardjito Hospital and Muhammadiyah kindergarten, Yogyakarta. Two structured questionnaires were used; the first identified the case group (asthma) and control group (nonasthma), whereas the second one identified whether the subjects had bottle feeding in supine position in the first year of life or not.Results 122 subjects were studied, 62 subjects in asthma groupand 60 in control group. In asthma group, feeding in supineposition before sleep time in the first year had OR of 2.45 (95%CI 1.21 to 6.93), whereas regurgitation when bottle-feeding insupine position had OR of 4.53 (95% CI 1.54 to 13.16). Suddencry when bottle-feeding in supine position had OR of 5.02 (95%CI 1.69 to 15.71). Asthma in the family increased risk of asthma[OR 3.12 (95% CI 1.16 to 6.50)] and atopicfamily has OR 3.25(95% CI 1.01 to 6.27).Conclusion Bottle feeding in supine position before sleep timeduring first year oflife is associated with occurrence of asthma inpreschool children.